2022
DOI: 10.3174/ajnr.a7455
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal MR Imaging Phenotype of Fetuses with Tuberous Sclerosis: An Institutional Case Series and Literature Review

Abstract: BACKGROUND AND PURPOSE: Most patients with tuberous sclerosis complex (TSC) do not receive prenatal diagnosis. Our aim was to describe MR imaging findings to determine the following: 1. Whether normal fetal MR imaging is more common in fetuses imaged at #24 weeks' gestation compared with .24 weeks 2. The frequency of cardiac rhabdomyoma 3. The range of MR imaging phenotypes in fetal tuberous sclerosis complex. MATERIALS AND METHODS:Our institutional fetal MR imaging data base was searched between January 1, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
8
0
6
Order By: Relevance
“…Cardiac rhabdomyomas are typically hyperintense on T2WI. In the brain, among the many T2-hypointense subependymal nodules found in children with TSC, they matched the criteria of SEGA in six cases ( Figure 4 c,d), i.e., were located in the foramen of Monro and had more than 10 mm in diameter [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac rhabdomyomas are typically hyperintense on T2WI. In the brain, among the many T2-hypointense subependymal nodules found in children with TSC, they matched the criteria of SEGA in six cases ( Figure 4 c,d), i.e., were located in the foramen of Monro and had more than 10 mm in diameter [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported [10] that the detection ability of MRI for intracranial lesions during fetal period and after birth is equivalent, which is adequate to accurately evaluate the intracranial condition of fetuses with TSC. Goergen et al [11] reported 42 TSC fetuses with cranial MRI, of which 57.8% with subependymal nodules, and 37% with cortical and subcortical lesions. In our study, 6/9 cases with TSC2 gene mutation (66.7%) had abnormal cranial MRI manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…8 ), gray matter heterotopia, and subependymal giant cell astrocytomas (SEGAs) which occur in late childhood in 10–15% of patients [58] . A recent literature review established fetal MRI detection rates for subependymal nodules and cortical/subcortical lesions at approximately 60% and 37%, respectively [59] . Prenatal diagnosis of such abnormalities has prognostic significance, as total lesion burden is associated with delays in cognitive and motor development, and with autism spectrum disorder 33640330 [60] .…”
Section: Hereditary Cancer Syndromesmentioning
confidence: 99%
“…Cardiac rhabdomyoma is often the first radiologic finding in TSC, and can be detected on fetal ultrasound between 20 and 30 weeks gestation [64] ; fetal MRI is also highly sensitive, particularly with increasing gestional age, and may reveal cardiac rhabdomyoma in up to 94% of examinations [59] . Spontaneous regression is observed in up to 70% of patients by age 4, but surveillance to resolution is recommended as rare serious complications such as heart failure, valvular dysfunction, and arrhythmia can occur [58] , [64] .…”
Section: Hereditary Cancer Syndromesmentioning
confidence: 99%